CLINICAL ANAMNESTICAL AND INSTRUMENTAL CHARACTERISTICS OF THE HIDDEN PENIS IN CHILDREN (SINGLE-CENTER PROSPECTIVE STUDY OF 106 OBSERVATIONS) - T.Kh Tojiyev; S.T. Agzamkhodjaev (Journal of modern medicine, 2026)
Justification. A hidden penis in children is more often associated with an excess of pubic tissue than with a pathology of the organ itself; however, the quantitative clinical and instrumental characteristics of this cohort are few in Russian-language literature, and there are no specialized works in Uzbekistan. The distinction between concealment and the true small organ is based on measurement and radiological diagnostics, rather than the first impression upon examination. Goal. Give a clinical-anamnestic and instrumental characterization of the penis and scrotal organs in children with a hidden penis based on examination, anthropometry, ultrasound examination with Doppler ultrasonography, and uroflowmetry. Material and methods. A prospective examination was conducted on 106 boys aged 1 to 17 (average age 5.9 years) who underwent surgery in the urology department of the NDMC between 2021 and 2026. The anamnesis, nutritional status in units of standard deviation of body mass index (SDS), elongated length of the penis, concealment index (threshold 0.68), ultrasound examination of the scrotum and penis with Doppler, uroflowmetry and pediatric scale of penis perception (PPPS) were assessed. Results. 46 children (43.4%) had excess body weight, and 30 (28.3%) had grade 2–3 obesity. Previously performed circumcision was noted in 31 children (29.2%). Pronounced pubic fatty tissue was present in 104 out of 106 children, while shifted attachment of the hanging ligament to the middle third of the trunk was observed in 93 (87.7%). The median concealment index was 0.64. The structure and blood supply of the testis and appendix are unchanged: the resistance index is normal for the age group, and the blood flow in the testicular artery is low-resistance monophase. The true length of the trunk corresponded to age, while the visible one was significantly smaller; in the 5–9 year group, the difference with healthy peers reached 4.1 cm. Uroflowmetry excluded obstruction: normal flow type in 56.6% of children, maximum speed at sufficient filling of 24.5–25.9 ml/s. Before surgery, the children's own assessment of PPPS (3.21 ± 1.41 points out of 12) was stricter than that of parents (4.21 ± 1.77) and surgeons (4.37 ± 1.61). Conclusion. Local penis in children is a pathology of soft tissues rather than the organ itself or its vascular bed: the trunk is formed, blood supply is complete, and it has a normal length, with only a part of it exposed to the outside. The leading factor is excess body weight, but the depth of immersion is determined by the skin-fascial and ligamentous apparatus. The cosmetic side suffers more than the functional one, which justifies the child's own participation in evaluating the result.